A salt-bridge switch in the molecular recognition between RS receptor and RGD ligand from the ABEEM σπ molecular dynamics simulations. Issue 13 (2nd November 2017) - Zhang, Chao; Zhao, Dong-Xia; Wang, Qian; Yu, Ling; Li, Guo-Hui; Yang, Zhong-Zhi
Abstract: How the receptor and ligand recognise each other is a challenging subject in explaining the mechanism of recognition at the molecular level. As a starting point, here, a synthesised RS receptor and its RGD ligand were investigated as a proper model to simulate their recognition process in terms of ABEEM σπ /MM polarisable force field. It is found that a switch of forming up a salt bridge in the ligand triggers the recognition of the receptor and ligand. Through the salt-bridge switch that undergoes several cycles from on-state with parallel hydrogen bonds to off-state with bifurcated hydrogen bonds, the active site of ligand can flex easily to interact with the active site of the receptor. In addition, the water molecules form a decisive bridge connecting the active sites of the bound system. The salt-bridge switch and water-mediated movement are cooperative as the important factors for the receptor-ligand recognition. In addition, the properties, such as binding free energy, conformational flexibility and solvent accessible surface area have been calculated to provide adequate evidence for the whole recognition process. According to the simulation, a detailed mechanism was derived involving diffusion, a switch triggered cooperative water-mediated movement, and conformational folding, for the flexible recognition.